2010
DOI: 10.1002/dev.20441
|View full text |Cite
|
Sign up to set email alerts
|

The influence of attachment representation on parental perception and interpretation of infant emotions: A multilevel approach

Abstract: The aim of the study was to investigate parental perception and interpretation of infant emotional expression depending on their attachment representation. Forty-six parents' responses to infant pictures depicting positive, neutral, and negative emotions were assessed on the level of affective judgments (valence, arousal), mimic responses (facial muscle activity), and of the eyelid reflex (using the startle paradigm). Results revealed small differences between parents of different attachment representations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
(61 reference statements)
1
15
1
1
Order By: Relevance
“…Consistent with this view, prior research has found adult attachment security to be linked with awareness and accurate labeling of infant emotions (Blokland & Goldberg, ; Deoliveira, Moran, & Pederson, ) and more positive and less negative personality attributions about distressed infants (Leerkes & Siepak, ; Zeanah et al., ). Likewise, adult attachment security has been linked with lower reported negative affect and better physiological regulation (Ablow et al., ), less physiological arousal (Groh & Roisman, ), and greater emotion mimicking in response to infant distress stimuli, which may reflect empathy (Spangler, Maier, Geserick, & von Wahlert, ).…”
Section: The Integrated Modelmentioning
confidence: 99%
“…Consistent with this view, prior research has found adult attachment security to be linked with awareness and accurate labeling of infant emotions (Blokland & Goldberg, ; Deoliveira, Moran, & Pederson, ) and more positive and less negative personality attributions about distressed infants (Leerkes & Siepak, ; Zeanah et al., ). Likewise, adult attachment security has been linked with lower reported negative affect and better physiological regulation (Ablow et al., ), less physiological arousal (Groh & Roisman, ), and greater emotion mimicking in response to infant distress stimuli, which may reflect empathy (Spangler, Maier, Geserick, & von Wahlert, ).…”
Section: The Integrated Modelmentioning
confidence: 99%
“…However, there is accumulating evidence that infant distress cues elicit different neurological, physiological, and self-reported responses from adults than infant neutral and positive cues (Groh & Roisman, 2009; Swain et al, 2012). Moreover, there are individual differences in the extent to which adults find distress cues arousing and aversive based on their attachment-related experiences and schema (Groh & Roisman, 2009; Spangler, Maier, Geserick, & von Wahlert, 2010). As such, we believe infant distress activates a unique set of emotion schema which can compromise mothers’ ability to attend to, interpret, and respond effectively to their infant.…”
Section: Differentiating Forms Of Maternal Sensitivitymentioning
confidence: 99%
“…Referring to Lang's (1995) theory, an infant's crying might simultaneously activate two motivational systems: the appetitive and the aversive. Infant crying as an unpleasant stimulus invokes negative emotions linked with perceived threat or danger, but at the same time, this is a strong indicator of need of support, and thus possesses an essential social function (Spangler, Maier, Geserick, & von Wahlert, 2010). Therefore, studies show individual differences in perceived aversiveness or in differentiability of parental (maternal) reactions to infant crying, ranging from empathy, through anxiety, to aversive responses (Del Vecchio, Walter, & O'Leary, 2009).…”
Section: Introductionmentioning
confidence: 99%